2020
DOI: 10.3390/membranes11010006
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Performance Analysis of the Steam Reforming of Methane in a Fixed Bed Membrane Reformer: A Modelling and Simulation Study

Abstract: Pd-based membrane reformers have been substantially studied in the past as a promising reformer to produce high-purity H2 from thermochemical conversion of methane (CH4). A variety of research approaches have been taken in the experimental and theoretical fields. The main objective of this work is a theoretical modelling to describe the process variables of the Steam Reforming of Methane (SRM) method on the Pd-based membrane reformer. These process variables describe the specific aims of each equation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It is possible to transform the equations system, Equations ( 1)-( 14), applying Equations ( 20)-( 21) using the boundary conditions of each EDP (Medeiros et al, 2021). Thus, transformed equations are reported as follows.…”
Section: Application Of the Ciea Methodologymentioning
confidence: 99%
“…It is possible to transform the equations system, Equations ( 1)-( 14), applying Equations ( 20)-( 21) using the boundary conditions of each EDP (Medeiros et al, 2021). Thus, transformed equations are reported as follows.…”
Section: Application Of the Ciea Methodologymentioning
confidence: 99%
“…The results showed that when the reaction and separation sections are decoupled such as RMM, the overall conversion of methane is increased by nearly 30%, which in turn improves the system efficiency. de Medeiros et al 108 conducted a modeling and simulation study to evaluate the thermochemical performance analysis of fixed bed reformer (FBR) and packed‐bed membrane reformer (PBMR). The developed models were validated with experimental data.…”
Section: Modeling Approaches For the Mrsmentioning
confidence: 99%
“…The membrane reactor has attracted significant attention owing to its compactness, fast response time, and high hydrogen yield 6‐9 . This latter can be affected by the chemical equilibrium shift in the SMR and the involved side reactions, especially the water gas shift (WGS) reaction that is deemed very weak in conventional reactors 10‐12 . Thus, the membrane helps to decentralize the system by reducing the number of separation modules and affords fast response times.…”
Section: Introductionmentioning
confidence: 99%
“…They showed an increase in the hydrogen recovery and methane conversion by 6.8% and 19.8%, respectively. Medeiros et al 43 conducted a parametric study on packed and fixed‐bed membrane reactors for SMR operations. The results showed several impacts of the operating conditions, that is, lowering the steam‐to‐carbon ratio can decrease the reactor outlet temperature and prompt carbon formation on the catalyst particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation